ЗАРОДЖЕННЯ ІДЕЙ УНІВЕРСАЛЬНОГО ДИЗАЙНУ В УКРАЇНІ - Творонович, Ігор (Містобудування та територіальне планування, 2024)
This text describes the development and emergence of the ideas of accessibility, inclusiveness, and universal design in the time of independent Ukraine. The basic principles of universal design developed by R. Mace's team and the initial state of the trend's development within the Ukrainian social and political field (discourse) are described. The difference and local peculiarities of the use of the terms "barrier-free environment", "inclusion" and "universal design", "accessibility" in the Ukrainian social field are also identified and described. Examples are also given and the first material embodiments of accessibility principles in the architectural environment of Ukraine are described. A brief analysis of the possible development of the trend of inclusion and accessibility in the structure of Ukrainian architectural and social discourses is also provided. The increase in the number of people with disabilities caused by natural, social and man-made causes, on the one hand, and the low quality of the culture of universal design of state and public institutions in modern Ukraine, on the other hand, leads to a growing need to introduce a culture of inclusion to address numerous problems that limit inclusiveness.